Benefit‐risk assessment of nivolumab 240 mg flat dose relative to 3 mg/kg Q2W regimen in Japanese patients with advanced cancers. Issue 2 (21st January 2020) - Bei, Di; Osawa, Mayu; Uemura, Shinji; Ohno, Tomoya; Gobburu, Jogarao; Roy, Amit; Hasegawa, Mayumi
Abstract: Nivolumab 3 mg/kg every 2 weeks (Q2W) has been approved in Japan for various cancers; however, use of a flat dose is expected to simplify dosing and administration. A quantitative clinical pharmacology approach was used to assess the benefit‐risk profile of nivolumab 240 mg Q2W relative to the approved dose of nivolumab 3 mg/kg Q2W in Japanese patients. Three exposure‐response safety analyses were performed for adverse events that led to discontinuation/death, were grade 3 or higher, and were immune‐mediated and grade 2 or higher for Japanese patients diagnosed with one of multiple tumor types. Exposure‐response analyses of efficacy were evaluated for overall survival and objective response rate. Exposures of nivolumab 240 mg Q2W were 37% higher than those of nivolumab 3 mg/kg Q2W in Japanese patients across the tumor types analyzed. Predicted safety profiles at the two doses differed by less than 2% across tumor types for adverse events leading to discontinuation/death, adverse events of grade 3 or higher, or immune‐mediated adverse events of grade 2 or higher. In addition, the predicted 1‐year and 2‐year overall survival rates, the mean overall survival and the objective response rates were comparable between the doses regardless of the tumor type analyzed. Overall, these results demonstrated that the benefit‐risk of nivolumab 240 mg Q2W was comparable to that of the previously approved 3 mg/kg Q2W dosing regimen, and was the basis for the approval of the 240 mg Q2W as an alternative dosing regimen for treatment in Japanese patients across multiple tumor types. Abstract : Exposure‐response analyses of nivolumab in Japanese patients indicate comparable safety and efficacy outcomes for a flat dose of 240 mg every 2 weeks relative to the previously approved weight‐based dose of 3 mg/kg. These data suggest that a flat dose is a safe and effective alternative to the weight‐based dose in Japanese patients, across a range of tumor types.